2006
DOI: 10.1002/jnr.20849
|View full text |Cite
|
Sign up to set email alerts
|

Neudesin, a secreted factor, promotes neural cell proliferation and neuronal differentiation in mouse neural precursor cells

Abstract: Neudesin encodes a secreted signal with neurotrophic activity in neurons. Most neurotrophic factors are involved in neural cell proliferation and/or differentiation. However, the role of neudesin in neural development remains to be elucidated. We examined the expression of neudesin in mouse embryonic cerebral cortex and cultured mouse neural precursor cells and its roles in neural development. Neudesin was expressed in the embryonic cerebral cortex early in development. Its expression was observed mainly in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 27 publications
2
70
0
Order By: Relevance
“…Comparison of all secreted proteins or proteins predicted to be secreted according to the literature revealed that USSC secrete at least 31 proteins that are known to be involved in neurite growth or axonal regrowth (Table I) including the neurotrophic factors mesencephalic astrocyte-derived neurotrophic factor (MANF) (37), neudesin (38), and neuron-derived neurotrophic factor (NDNF) (39) as well as the growth factors angiopoietin-2 (40), growth/differentiation factor 15 (GDF-15) (41), hepatoma-derived growth factor (HDGF) (42), PDGF (43), and transforming growth factor-beta1/-2 (TGF-␤1/TGF-␤2) (44 -45). Moreover, we identified several matrix-and membrane-associated proteins, e.g.…”
Section: Characterization Of Ussc Secretome By Mass Spectrometry-mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of all secreted proteins or proteins predicted to be secreted according to the literature revealed that USSC secrete at least 31 proteins that are known to be involved in neurite growth or axonal regrowth (Table I) including the neurotrophic factors mesencephalic astrocyte-derived neurotrophic factor (MANF) (37), neudesin (38), and neuron-derived neurotrophic factor (NDNF) (39) as well as the growth factors angiopoietin-2 (40), growth/differentiation factor 15 (GDF-15) (41), hepatoma-derived growth factor (HDGF) (42), PDGF (43), and transforming growth factor-beta1/-2 (TGF-␤1/TGF-␤2) (44 -45). Moreover, we identified several matrix-and membrane-associated proteins, e.g.…”
Section: Characterization Of Ussc Secretome By Mass Spectrometry-mentioning
confidence: 99%
“…PDGF and TGF-␤1, both secreted by USSC, are known to interact with SPARC (64 -66), indicating a solid network between the secreted factors. Moreover, USSC secrete MIF, which directs the initial neurite outgrowth from the statoacoustic ganglion (SAG) to the developing inner ear (56), and NDNF, which could together with MANF, HDGF, and neudesin stimulate neurite growth as well as migration, cell growth, and survival (37)(38)(39)42). Recently, periostin, which is normally expressed in bone and muscles, has been shown to play an essential role in neurite growth and axonal regeneration after SCI to overcome the inhibitory effect of scar-associated molecules by signaling through focal adhesion kinase and Akt (67).…”
Section: Stimulation Of Neurite Growth By Application Of Candidate Nementioning
confidence: 99%
“…Neudesin is the novel secreted protein that we previously identified as a neurotrophic factor (12,13). Mouse neudesin exhibited high similarity (ϳ90% identity) to human and rat neudesins.…”
mentioning
confidence: 99%
“…This may be because Neudesin and Neferricin are present in the luminal compartment and secreted extracellularly (2,3,(24)(25)(26)(27)(28), however the presence of some observed phosphorylation events suggests that the MAPR domain of these proteins may also be found in the cytoplasm. The detection of O-N-acetylgalactosamine (O-GalNAc) glycosylation does not necessarily imply an extracellular location for Neudesin, since 14% of O-GalNAc proteins are annotated with nuclear Gene Ontogeny (GO) assignments (29).…”
Section: Posttranslational Modifications Of Neudesin and Neuferricinmentioning
confidence: 83%